Analysis of the Application of Draping Techniques in Education and the Fashion Industry: An Approach from Dress Design to Interactive Learning - Farihah, Farihah; Siregar, Dina Mutiara; Sinaga, Ermitati; br Sitepu, Feby Adelvia; Haniyah, Meysi Asma; Aritonang, Nabila Mahliza; Tumangger, Nita Oktaria; Hutajulu, Ribka R. (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the application of draping techniques in the context of education and the fashion industry, focusing on their effectiveness in the dress design process and their contribution to interactive learning. The study was conducted using quantitative and qualitative descriptive approaches. The research sample consisted of 30 Fashion Design students and 10 professional designers. Data collection techniques were carried out through observation of the learning process, questionnaires, interviews, and documentation of draping-based fashion design results. The results showed that students who learned using the draping technique obtained an average score of 82.3 (out of a scale of 100) in design skills, with a standard deviation of 6.4, indicating a fairly even increase in ability. Meanwhile, in the industrial context, the average time to make a prototype using the draping technique was 4.8 days, with a standard deviation of 1.1 days, more efficient than the flat pattern construction technique which took an average of 6.2 days (SD = 1.3 days). These findings confirm that the draping technique not only improves students' creativity and spatial understanding, but also contributes to efficiency and innovation in the fashion production process. Therefore, this study recommends strengthening the integration of draping techniques in the fashion education curriculum and increasing synergy between educational institutions and industry players to create interactive and applicable learning.